From window guidance to interbank rates: Tracing the transition of monetary policy in Japan and China - Stefan Angrick; Yoshino Naoyuki (Bank of Finland, Institute for Economies in Transition (BOFIT), 2018)
Monetary policy in most major economies has traditionally focused on control of the interbank interest rate to achieve an inflation target. Monetary policy in transition economies, in contrast, relied on a mixed system of price-based and quantity based instruments and targets. Japanese monetary policy up to the 1990s was based on such a mix, and echoes of this system are today found in China's monetary policy set-up. We explore the transition of these two monetary policy regimes historically and quantitatively with institutional comparison and Structural Vector Autoregressive (SVAR) models. Specifically, we examine the role of the interbank rate and "window guidance," a policy by which authorities use "moral suasion" to communicate target quotas for lending growth directly to commercial banks. In Japan's case, we compile historical statistics on window guidance from newspapers and industry sources. For China, we apply Romer–Romer text analysis and computational linguistic techniques to policy reports to quantify information on window guidance.We empirically demonstrate the declining effectiveness of quantity measures and the increasing importance of price measures. We end with a policy assessment of managing the transition of monetary policy from a quantity-based system to a price-based system.
URN:NBN:fi:bof-201802211230
Keywords: E5; E52; E58; 330